2016 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2016
DOI: 10.1109/smc.2016.7844637
|View full text |Cite
|
Sign up to set email alerts
|

Fast content-based image retrieval using convolutional neural network and hash function

Abstract: Abstract-Due to the explosive increase of online images, content-based image retrieval has gained a lot of attention. The success of deep learning techniques such as convolutional neural networks have motivated us to explore its applications in our context. The main contribution of our work is a novel endto-end supervised learning framework that learns probabilitybased semantic-level similarity and feature-level similarity simultaneously. The main advantage of our novel hashing scheme that it is able to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It has been shown that the features extracted using a pretrained CNN are rich and effective for a wide range of computer vision and image processing tasks, such as content-based image retrieval [35], NR image quality assessment [2], and medical image classification [10]. The main contribution and novel aspect of the present study is that we obtain possible solutions for NR-VQA using only the deep features extracted from pretrained CNNs (Inception-V3 [32] and Inception-ResNet-V2 [31]) without depending on manually selected features.…”
mentioning
confidence: 99%
“…It has been shown that the features extracted using a pretrained CNN are rich and effective for a wide range of computer vision and image processing tasks, such as content-based image retrieval [35], NR image quality assessment [2], and medical image classification [10]. The main contribution and novel aspect of the present study is that we obtain possible solutions for NR-VQA using only the deep features extracted from pretrained CNNs (Inception-V3 [32] and Inception-ResNet-V2 [31]) without depending on manually selected features.…”
mentioning
confidence: 99%
“…In addition, dimension reduction can solve the multicollinearity problem by removing redundant features, which is helpful for data visualization. If the dimensions of the data are very high, visualization becomes quite difficult, whereas drawing two-and three-dimensional data is simpler [18]. is paper mainly studies manifold learning-based image dimension reduction algorithm and feature-based image matching algorithm.…”
Section: Contents and Methodsmentioning
confidence: 99%
“…The content-based image retrieval (CBIR) is used visual features including image edge, name suitability, color, and texture in input images [ 46 ]. The CNN is applied for image classification to retrieve images using cosine similarity.…”
Section: Related Workmentioning
confidence: 99%